1998
DOI: 10.1083/jcb.140.3.499
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-1 Modification and Its Role in Targeting the Ran GTPase-activating Protein, RanGAP1, to the Nuclear Pore Complex

Abstract: RanGAP1 is the GTPase-activating protein for Ran, a small ras-like GTPase involved in regulating nucleocytoplasmic transport. In vertebrates, RanGAP1 is present in two forms: one that is cytoplasmic, and another that is concentrated at the cytoplasmic fibers of nuclear pore complexes (NPCs). The NPC-associated form of RanGAP1 is covalently modified by the small ubiquitin-like protein, SUMO-1, and we have recently proposed that SUMO-1 modification functions to target RanGAP1 to the NPC. Here, we identify the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
394
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(412 citation statements)
references
References 60 publications
12
394
1
2
Order By: Relevance
“…The predicted common SUMO site for RGS-Rz proteins is located at the end of the RGS a4 helix, and the specific site in RGSZ2 is at the beginning of a3. Both these regions belong to this potential regulatory site; consistent with the idea that sumoylation may modulate protein-protein interactions (Matunis et al, 1998) and subcellular localization (Sobko et al, 2002). It is therefore possible that SUMO conjugation impedes or even disrupts the GAP activity of RGS-Rz proteins on receptor-activated Gaz/i2 subunits.…”
Section: Discussionsupporting
confidence: 80%
“…The predicted common SUMO site for RGS-Rz proteins is located at the end of the RGS a4 helix, and the specific site in RGSZ2 is at the beginning of a3. Both these regions belong to this potential regulatory site; consistent with the idea that sumoylation may modulate protein-protein interactions (Matunis et al, 1998) and subcellular localization (Sobko et al, 2002). It is therefore possible that SUMO conjugation impedes or even disrupts the GAP activity of RGS-Rz proteins on receptor-activated Gaz/i2 subunits.…”
Section: Discussionsupporting
confidence: 80%
“…It was further demonstrated that loss of a single Rae1 allele causes a mitotic checkpoint defect and chromosome missegregation (Babu et al, 2003). It was also recently shown that SUMO-1 modified RanGAP1 and RanBP2/Nup358, which are associated with the cytoplasmic face of NPCs in interphase, are targeted as a complex to kinetochores and mitotic spindles in mitosis (Matunis et al, 1998;Joseph et al, 2002Joseph et al, , 2004. RNA interference approaches in Caenorhabditis elegans early embryo and HeLa cells further revealed the involvement of RanBP2/ Nup358 in chromosome congression and segregation, stable kinetochore-microtubule association, and kinetochore assembly (Askjaer et al, 2002;Salina et al, 2003;Joseph et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Around the same time, another report implicated SUMO (referred to as sentrin) as a molecule that modified responses triggered by cell-death receptors [2]. Later, the modification by M-SUMO-1 was shown to be critical for the localization of RanGAP-SUMO-1 to the nuclear pore complex [3]. Since its original discovery, SUMO has been cloned from an array of eukaryotic organisms, including animals, fungi and plants.…”
Section: Introductionmentioning
confidence: 99%